Réponses

2014-02-27T19:07:24+01:00
A) -3x²-x²+7x-9+6x
    -3x²-x²+7x+6x-9
     -4x²+13x-9

b) -2x+11-4x²-8x²-5x+17
   -4x²-8x²-2x-5x+11+17
   -12x²-7x+28
Meilleure réponse !
2014-02-27T19:08:48+01:00

A= -3x² - x² + 7x - 9 + 6x

A= -3x² - x² + 7x + 6x - 9

A= -4x² + 13x - 9


B= -2x + 11 - 4x² - 8x² - 5x + 17

B= -4x² - 8x² - 2x - 5x + 11 + 17

B= -12x² - 7x + 28


C= 2x² - 3x + 4 - 5x² + 6x - 8

C= 2x² - 5x² - 3x + 6x + 4 - 8

C= -3x² + 3x - 4


Je l'ai rajouté
ou?
A C BON MERCI BCP
De rien, tu n'aurais pas du faire un nouveau devoir juste pour ça :/
OUI JAVOUE MAIS C PAS GRAVE ;)